OPTIMALISASI PERAN GENERASI MILLENIAL DALAM MENGEMBANGKAN KEWIRAUSAHAAN BERBASIS DIGITAL (STUDI KASUS USAHA ONLINE BUCKET DAN HAMPERS) - Fadlatul Wasilah; Asep Kholidul Mufid; Irfan Rosidi; Ninik Ariesta Zulfani; Ani Faujiah (ICO EDUSHA, 2021)
Indonesia is currently still facing challenges in developing a digital economy. This requires the participation of the millennial generation in developing the digital economy. The millennial generation is the generation born at the time of the increasingly rapid technological developments in human life, namely between 1977-1994. The millennial generation has an important role in the development of the digital economy. One of the efforts that the millennial generation can take is to develop entrepreneurship based on digital technology. This study uses a qualitative descriptive research method with an analytical study approach. The data collection techniques that researchers use include observation and interviews. The results showed that 90% of sales were made through online media and the remaining 10% was door to door to consumers. The strategies used by the two resource persons were creating interesting social media content, giving gifts, doing promotions on certain days and holding giveaways. The challenges faced are the ups and downs of consumers, a decline in demand due to the Covid-19 pandemic, some mistake from business actors, and errors from suppliers (goods providers). Keywords: Millennial Generation, Entrepreneur, Digital References Ambarwati, dan Indra Sumarna Sobari. “Membangun Jiwa Kewirausahaan di Era Millenial bagi Mahasiswa Institut Stiami Kampus Tangerang Selatan.” Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat 2 (Januari 2020). Annisa, Siti Noer. Wawancara, 11 Desember 2021. Azizah, Nurul Safura. “Pengaruh Literasi Keuangan, Gaya Hidup pada Perilaku Keuangan Generasi Millenail.” Prisma (Platform Riset Mahasiswa Akuntansi 01 (31 Maret 2020). Bayti, Tety Nur. Gagasan Millenial dan Generasi Z Untuk Indonesia Emas 2045. Atambua Barat: Fianosa Publishing, 2020. Ernawati, Yenni. “Komik Digital Ekonomi Untuk Generasi Milenial.” Jurnal Education and development 08 (Mei 2020). Fitriyadi, Enjah Pipit. “Inovasi E-commerce dan Startup Sebagai Tantangan Masyarakat Industri 4.0.” Jurnal Teknologi Informasi ESIT 14 No 2 (2019). Guthrie, Cameron. “The digital factory: a hands-on learning project digital entrepreneurship.” Journal of Entrepreneurship Education 17 No1 (2014). Hasan, Muhammad, Nur Arisah, Fira Ayu Sasmita, Miranda, Aisyah Amailiah Putri, dan Chatrien Dione Pattisina. “Perilaku Berwirausaha Generasi Millenial di Era Pandemi COVID-19.” Jurnal Pendidikan Ekonomi Undiksha 13 (2021). Murti, Nuriska Listyo. “Strategi Marketing Door to Door dalam Meningkatkan Jumlah Anggota BMT Al-Hikmah Cabang Gunungpati Sekaran.” Universitas Islam Negeri Walisongo, 2017. Qotrunnida, Nirmala. Wawancara, 11 Desember 2021. Santoso, Amanda Putri. “Pengaruh Konten Instagram terhadap online engagement.” Institut Teknologi Sepuluh November, 2017. Sundari, Cisilia. “Revolusi Industri 4.0 merupakan peluang dn tantangan bisnis bagi generasi milenial di Indonesia,” 15 Oktober 2019. Wirapraja, Alexander. “Pemanfaatan E-Commerce Sebagai Solusi Inovasi Dalam Menjaga Sustainability Bisnis.” Teknika 7 Nomor 1 (Juli 2018).